5(m-4)=2m+3

Simple and best practice solution for 5(m-4)=2m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m-4)=2m+3 equation:


Simplifying
5(m + -4) = 2m + 3

Reorder the terms:
5(-4 + m) = 2m + 3
(-4 * 5 + m * 5) = 2m + 3
(-20 + 5m) = 2m + 3

Reorder the terms:
-20 + 5m = 3 + 2m

Solving
-20 + 5m = 3 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
-20 + 5m + -2m = 3 + 2m + -2m

Combine like terms: 5m + -2m = 3m
-20 + 3m = 3 + 2m + -2m

Combine like terms: 2m + -2m = 0
-20 + 3m = 3 + 0
-20 + 3m = 3

Add '20' to each side of the equation.
-20 + 20 + 3m = 3 + 20

Combine like terms: -20 + 20 = 0
0 + 3m = 3 + 20
3m = 3 + 20

Combine like terms: 3 + 20 = 23
3m = 23

Divide each side by '3'.
m = 7.666666667

Simplifying
m = 7.666666667

See similar equations:

| -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 | | (p/2)/2 |

Equations solver categories